Effect of feeding frequency on feed consumption, growth and feed conversion of Tor tambroides (Empurau) - Sharifah Khadijah, binti Syed Ismail (Universiti Malaysia Sarawak (UNIMAS), 2012)
The effect of feeding frequency on feed consumption, growth and feed conversion efficiency of Tor tambroides (Empurau) was investigated over a period of 10 weeks. There were significant difference (P<O.05) in feed consumption at the different feeding frequencies. There was significant difference (P<O.05) in final fish length between these feeding frequencies. Fish in feeding frequency A (once daily) and frequency E (five times daily) show significant difference in length. There was also a significant difference (P<O.05) in final weight values at the different feeding frequencies. The highest length increment (4.26±O.12 em) was observed in feeding frequency E and the lowest length increment (2.66±O.24 cm) observed in frequency A. Likewise, the highest weight increment (6.22±O.OO g) was recorded at the highest feeding frequency (E) and the lowest value (4.48±O.09 g) was recorded at the lowest feeding frequency (A). The fish fed at frequencies of five times daily had the highest feed conversion ratios and the least feeding conversion efficiencies (4.47, 22.36%) and the ones fed once and twice daily had the lowest feed conversion ratios and the highest feed efficiencies (1.53, 2.33 and 65.26%,42.97%, respectively). A statistical comparison between the means of FCR using ANDY A revealed a significant difference (P<O.05) among the feeding frequencies. It was concluded that feeding Tor lambroides more than once a day increased growth performance and feed conversion ratio was better in once and twice daily feeding.